Monte Carlo Simulations Of Avalanche Multiplication, Noise And Speed In Submicron InP - You , Ah Heng (2005)
A stochastic nature of avalanche photodiode (APD) model is developed using Monte Carlo method to study the avalanche characteristics in submicron InP p= -i- n+ diodes. The avalanche characteristics such as multiplication gain, excess noise factor and avalanche built-up time in submicron InP p+ -i-n+ diodes are presented. A realistic FUll Band Monte Carlo (FBMC) model using empirical local pseudopotential band structure is used to simulate multiplication gain, excess noise factor and time response of InP p+ -i-n+ diodes. A simple and fast Random Path Length (RPL) model incorporating the dead-space effect is developed to reproduce the avalanche characteristics of short InP p+ -i-n+ diodes.